Life and death of Krishnamurthi - "Lutyens, Mary" (London, 1990)
With Krishnamurti's death in 1986, aged 90, Mary Lutyens was able to complete her perceptive books on this extraordinary man. Only now has she been able, in this one-volume biography, to bring his life into true perspective. It is a brief but absorbing account of Krishnamurti's life, and in it she seeks to understand his death (and Death itself) in terms of his own words on the subject. The author claims no more than to introduce Krishnamurti's teaching, but by studying his own explorations into its origin, she is able to give help to the reader who wishes to delve deeper, as many will. Having known him from the time he first came to England as a new Messiah under the aegis of the Theosophical Society, from which he dramatically broke away in 1929, no one is better qualified than Mary Lutyens to see Krishnamurti's life as a whole and to search for an answer to the question. 'Who or what was Krishnamurti?' He was himself specific as to what he was not: he was no guru and deplored the very existence of a guru-disciple relationship; he was the leader of no religious organization-he maintained that all such organizations were barriers to truth and that what he had to say was equally relevant to all. It was his object to set us free from everything that prevents us from discovering truth for ourselves. Krishnamurti sought to bring understanding, not comfort. An austere philosophy, but a subtle one which stimulated hundreds of thousands of people in many parts of the world to seek to bring about a complete psychological change in themselves as the only means of ending violence and sorrow. Schools and centres were founded in his name in Europe. America and India which spread this teaching throughout the world. Krishnamurti emerges from this book as not only a phenomenal teacher but as a man with deep affections and a love of laughter.
Keywords: "Krishnamurti, Jiddu-Biography"